Complete mitochondrial genome and phylogenetic analysis of Triplophysa jianchuanensis (Cypriniformes: Cobitidae) - Yonglan Peng; Yuping Qiu; Guozhu Chen (Mitochondrial DNA. Part B. Resources, 2023)
AbstractWe used the Illumina MiSeq platform to sequence the complete mitochondrial genome of Triplophysa jianchuanensis (Cypriniformes: Cobitidae). The mitochondrial genome of T. jianchuanensis is 16,569 bp in length, and its genetic constitution and arrangement are consistent with those of the teleost taxon, containing 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, an origin of light-strand replication, and a control region. The overall nucleotide base composition was 28.33% A, 27.25% T, 17.77% G, and 26.65% C. Phylogenetic analysis showed that T. jianchuanensis was grouped with T. venusta. These findings are valuable for further studies on the evolution, genetic diversity, and taxonomy of Triplophysa.